1988
DOI: 10.1080/03670244.1988.9991033
|View full text |Cite
|
Sign up to set email alerts
|

Haitian street foods and their nutritional contribution to dietary intake

Abstract: My gratitude is also extended to the Directors and students of the fifteen private schools in which the survey was conducted for their cooperation and participation. Acknowledgement is given to Judy Baker and the staff of the Forage iii Testing Laboratory at Virginia Polytechnic Institute and State University for their assistance in the proximate analysis of the street food samples. Lastly, appreciation is felt for the encouragement, support and guidance given me by my parents throughout the project. I would e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…This group hypothesized that many low-income urban families would be even worse off without the availability of street foods (FAO, 1990). Webb and Hyatt (1988) found that street foods provide 15% of the recommended dietary intake for energy and 18% for protein in the diet of secondary school students in Port-au-Prince, Haiti. Oguntona and Kanye (1995) showed that street foods contribute 25% of the energy and 52% of the protein intake of a group of urban adolescents in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…This group hypothesized that many low-income urban families would be even worse off without the availability of street foods (FAO, 1990). Webb and Hyatt (1988) found that street foods provide 15% of the recommended dietary intake for energy and 18% for protein in the diet of secondary school students in Port-au-Prince, Haiti. Oguntona and Kanye (1995) showed that street foods contribute 25% of the energy and 52% of the protein intake of a group of urban adolescents in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies presented findings on the types of food groups sold in street foods for different countries. In Haiti, for example, 146 different street foods were identified in Port-au-Prince of which cereals and grains accounted for 28?0 %, fruit for 18?5 %, and sugars and syrups for 16?4 % (10) . In Abeokuta, 50 % of meat and fish, 60 % of legumes and an estimated 42-66 % of all major food groups came from street foods (12,13) .…”
Section: Food Groupsmentioning
confidence: 99%
“…In Haiti, street foods contributed 16 % of the protein RDA in secondary-school children (10) . In Nigerian adolescents, average daily protein intake (62 g) from street foods provided more than 50 % of the RDA (12) .…”
Section: Energy and Nutrient Intakesmentioning
confidence: 99%
See 2 more Smart Citations